A scoping review protocol on brain PaCO2 levels at altitude - Hanna Tang; Laurel Charlesworth; Manoj Lalu; Brian Dewar; Risa Shorr; Dariush Dowlatshahi (PLoS ONE, 2025)
Background Aeromedical transfer of patients with ischemic stroke to access hyperacute stroke treatment is becoming increasingly common. Little is known about how rapid changes of altitude and atmospheric pressure can impact cerebral perfusion and ischemic burden. In patients with ischemic stroke, there is a theoretical possibility that this physiologic response of hypoxia-driven hyperventilation at higher altitude can lead to a relative drop in PaCO2. This would ultimately result in cerebral vasoconstriction, and therefore worsening of the ischemic burden in patients with ischemic stroke. Currently, there are no specific recommendations in stroke guidelines for optimizing altitude of aeromedical transportation to minimize the rate of ischemic burden. In this scoping review, we aim to map the available literature that addressed whether PaCO2 changes with altitude. This would be the steppingstone for more in-depth analyses into the cerebral autoregulatory consequences of high altitude on cerebral ischemia to form future guidelines. Methods and analysis We will follow scoping review methods recommended by the Joanna Briggs Institute. Electronic databases MEDLINE, Embase, Web of Science, and Cochrane Central Register of Systematic will be systematically searched to identify articles that report on the acute response of PaCO2 on acute change in altitude. Two independent investigators will perform duplicate title and abstract screening and full-text review, followed by duplicate data extraction. We will present quantitative data using descriptive statistics. Key textual information will be synthesized in a tabular format Simple statistics on the frequency of papers, data will be presented via histogram. Ethics and dissemination This scoping review does not require ethical approval. The results of our scoping review will be published in academic medical journals and presented at medical conferences. The findings will highlight the current availability of literature on PaCO2 changes with altitude. Registration This scoping review protocol has been registered in Open Science Framework (DOI 10.17605/OSF.IO/UVK83).